Memicu Dialog Dinamis tentang Solusi Sehari-hari melalui Kartu Pemetaan Solusi - Taepoer, Raditya Ardianto; Ono, Kenta; Malasan, Prananda Luffiansyah; Triharini, Meirina; Puspita, Arianti Ayu; Sugandi, Yulia; Nurin, Bima (Aliansi Desainer Produk Industri Indonesia (ADPII), 2024)
The contemporary world is amid a dynamic and transformative phase characterised by fundamental shifts, leading to complex environmental, socioeconomic, healthcare, and social challenges. This convergence of multifaceted requires a holistic and innovative approach to ensure a sustainable and harmonious global future. Design for social innovation has introduced novel expertise and methodologies, leveraging the dynamics inherent in social systems to create impactful solutions by actively engaging stakeholders to understand contextual perspectives and minimise knowledge gaps. Solution Mapping Tools facilitate communities to delve into the significance of local needs and assets in addressing everyday societal challenges. Incorporate within these tools, Solution Mapping Cards foster dialogue and understanding by transforming abstract concepts into tangible representations. The main topic resulting from this article revolves around the evolving nature of design thinking, the role of designers in addressing complex problems, and the practical implications of using tools such as Solution Mapping Cards.